DEVELOPMENT OF IOT-BASED PRESENCE SYSTEM FOR SCHOOL USING PROTOTYPE METHOD (CASE STUDY: YPPMNU AJIBARANG) - Teguh Rijanandi; Ariq Cahya Wardhana; Rini Adelina Siagian (Jurnal Teknoinfo, 2023)
Today's rapid development of technology makes it easy to do everything from shopping to reading today's news to studying online and more. This technology has been widely used, for example in government agencies, schools, hospitals, clinics, and so on. Digital or computerized information technology can improve work efficiency. The technology present in the current era of globalization has developed, including attendance or attendance systems using fingerprints, irises, and RFID cards. Many large companies, SMEs, and schools take advantage of technological developments, therefore this research wants to implement IoT technology developments at YPPMNU Ajibarang because of the large number of employees, there are around 200 active employees. Moreover, the attendance itself is carried out every day, of course, the attendance data that they process is very large. The Ma`arif NU Education Organizing Foundation (YPPMNU) Ajibarang is a foundation engaged in education in the Ajibarang area. YPPMNU has four technical implementing units (UPT), Ma'arif NU 1 Ajibarang Vocational School, Ma'arif NU 2 Ajibarang Vocational School, Ibnu Sina Ajibarang STIKES, and Ibnu Sina Ajibarang Modern Islamic Boarding School, with an active number of around 200 active employees. YPPMNU already uses an information system called the YPPMNU Ajibarang Personnel Management Information System, which has functions such as employee capabilities. The pandemic has brought the work system from working directly from the office to working from home. Previously, YPPMNU had its own attendance system using a web-based application. This study aims to develop an IoT-based attendance system using the prototype method and evaluate an IoT-based attendance system using the UAT testing technique so that it can be well received by users. The research method used in this design is to use the prototype method. The results of this study are an evaluation of how the IoT-based attendance system uses the UAT method, and the IoT-based attendance system uses the prototype method.